Causes of Uncertain Chemotherapy Outcomes in Patients with Pulmonary Tuberculosis Treated in Penitentiary Institutions of the Russian Federation - S. N. Lisovskiy; M. E. Vostroknutov; Yu. V. Mikhaylova; S. A. Sterlikov; S. B. Ponomarev (Туберкулез и болезни лёгких, 2022)
Reporting of the «transferred out» outcome leads to significantly worse treatment results of tuberculosis patients treated in the institutions of the Federal Penitentiary Service of Russia.The objective: to investigate the patients’ routes that led to reporting of the «transferred out» outcome, and propose measures to reduce the risk of this outcome.Subjects and Methods. We studied the places of registration and routes of 1,496 pulmonary tuberculosis patients registered for treatment in 2019 (new cases and relapses) with the outcome of «transfered out».Results. In the structure of transferred out patients, in 631/1,496 (42.2%) patients, the «transferred out» outcome was associated with their transfer between institutions within the penitentiary system. Additionally 462/1,496 (30.9%) patients were released in the region where they continued their treatment, 85/1,496 (5.7%) were released and moved to a different region, 301/1,496 (20.6%) were released from pre-trial detention , and 10/1,496 (0.6%) left Russia and moved abroad.Conclusion: the procedure should be developed to transfer the information about patients moving within the penitentiary system and beyond it. To motivate the patient immediately after the detection of tuberculosis, it is necessary to conduct individual conversations explaining the nature of the disease, importance and necessity of treatment. Tuberculosis patients in pre-trial detention centers should be provided with leaflets containing information about medical organization where patients can continue treatment, patients released from penitentiary units should be informed about the system of social adaptation and services available for tuberculosis patients.